Early emergency care study: the potential and benefits of advanced prehospital care. Issue 6566 (24th January 1987) - Anderson, I W; Black, R J; Ledingham, I M; Little, K; Robertson, C E; Urquhart, J D
Abstract : Of 26358 patients taken by ambulance to the accident and emergency departments of two large hospitals, 1185 were admitted to resuscitation areas. The scope for ambulance staff to employ a range of advanced techniques at the scene of incidents was assessed by using information relating to the condition of patients when they were picked up by the ambulance and on admission, time in transit, details from hospital records, and outcome at three months. For non-survivors further assessment was made of the benefit, in terms of survival, which might have accrued had advanced techniques been used. The results of the assessment of benefit were compared with estimates of benefit from other studies. In cases of cardiopulmonary arrest the potential to save lives was less optimistic than earlier estimates, and in cases of trauma the potential to save lives was negligible.